A novel modified trans-umbilical open technique for secure laparoscopic entry through the natural umbilical defect: Sheredi’s technique - Sheredi, Mohamed A.; Jones, Stacey Jessica (International Surgery Journal, 2025)
Background: Safe and efficient entry into the peritoneal cavity is essential in laparoscopic surgery. The umbilicus is a preferred site for trocar insertion; however, the prevalence and surgical utility of a small physiological defect in the umbilical linea alba are poorly documented. This study describes a novel open-access method, Sheredi’s modified trans umbilical open technique-which utilizes this anatomical feature and assesses its prevalence. Methods: A prospective cohort study of 193 consecutive patients undergoing laparoscopic surgery by a single surgeon at the Mid Yorkshire NHS Trust between January 2020 and February 2023 was conducted. Open peritoneal entry was performed through a physiological umbilical linea alba defect, when present. Patients with umbilical or paraumbilical hernias, or with a history of prior umbilical surgery, were excluded. A prospectively maintained database captured demographic and operative data, including defect presence and size, access time, complications, and cosmetic outcomes. Associations between defect presence and age, sex, and BMI were analysed. Results: Of the 193 patients (median age 44 years; 81 males, 112 females), 124 (67%) had a physiological umbilical defect. There was no significant association between defect presence and age, sex, or body mass index (BMI). No bowel, vascular, or visceral injuries occurred. The mean access time was 1.2 minutes. Three patients (1.6%) developed surgical site infections (SSIs); all were smokers, and one had diabetes. All patients reported satisfaction with the cosmetic outcome. Conclusions: The author’s open technique is safe, rapid, and cosmetically favourable when a physiological umbilical defect is present, supporting its use as a primary peritoneal entry method in laparoscopic surgery.